Synthesis of (2-Aminopyrimidin-4-yl)(pyridin-4-yl)methanone and Derivatives - Giraud, Francis; Josselin, Béatrice; Ruchaud, Sandrine; Anizon, Fabrice; Moreau, Pascale (Synthesis, 2023)
Pyrido[3,4-g]quinazoline was previously identified as a relevant scaffold for protein kinase inhibition. In order to assess if the planarity of this heterocyclic system was essential to the protein kinase inhibitory potency observed in this series, new compounds were synthesized and evaluated, in which the central cycle was opened to provide (pyridin-4-yl)(pyrimidin-4-yl)methane derivatives, which were prepared from the corresponding ketone precursor. After preparing (2-aminopyrimidin-4-yl)(pyridin-4-yl)methanone, derivatives were synthesized and evaluated toward a panel of protein kinases. The results demonstrated that the planar pyrido[3,4-g]quinazoline tricyclic system was mandatory to maintain the protein kinase inhibitory potency in this series.
Keywords: diheteroaryl ketone; pyrido[3,4-g]quinazoline; (pyrimidin-4-yl)(pyridin-4-yl)methanone; Grignard reagents; molecular shape; protein kinase inhibitors